2017
DOI: 10.3390/app7020197
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Hybrid Photovoltaic Solar Assisted Loop Heat Pipe/Heat Pump System

Abstract: Abstract:A hybrid photovoltaic solar assisted loop heat pipe/heat pump (PV-SALHP/HP) water heater system has been developed and numerically studied. The system is the combination of loop heat pipe (LHP) mode and heat pump (HP) mode, and the two modes can be run separately or compositely according to the weather conditions. The performances of independent heat pump (HP) mode and hybrid loop heat pipe/heat pump (LHP/HP) mode were simulated and compared. Simulation results showed that on typical sunny days in spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The study presented herein is based on the work previously reported by Yang et al [1], and references [2][3][4][5][6][7][8][9][10][11][12][13][14] where a flat plate solar collector is attached to a PV panel. The hybrid system in question is composed of the PV solar panel and thermal solar tube collector as well as a heat pump as shown in Figure 1.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The study presented herein is based on the work previously reported by Yang et al [1], and references [2][3][4][5][6][7][8][9][10][11][12][13][14] where a flat plate solar collector is attached to a PV panel. The hybrid system in question is composed of the PV solar panel and thermal solar tube collector as well as a heat pump as shown in Figure 1.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…New PV technologies reported in the literature have been shown to improve the energy utilization efficiency of solar PV, such as multi-junction cells, optical frequency shifting, and concentrated photovoltaic (CPV) systems, among others; however, these are expensive. In order to improve the efficiency of solar PVs a novel concept of a combined photovoltaic-thermal solar panel hybrid system has been developed and implemented [3][4][5][6][7][8][9], where the PV cells of the solar PV panels are cooled by water flow. Excess thermal energy is generated and dissipated due to intrinsic limitations of the cell, that is, the excess thermal energy increases the cell temperature, which reduces the conversion efficiency of the cell.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al [18] proposed a self-optimizing control scheme using the ESC (extremum seeking control) strategy which could search and even track both fixed and slowly varying optimum COP. Dai et al [19] numerically studied a hybrid solar assisted loop heat pipe/heat pump water heater system, and the results showed that, on typical sunny days in spring or autumn, the proposed system could save 40.6% power consumption compared to heat pump mode. The influence of wet compression on a heat pump system was experimentally investigated by Seong et al [20], who found that the heating capacity and power input of wet compression increased more than that of dry compression, with a superheat of 10 • C.…”
Section: Introductionmentioning
confidence: 99%